PPP exposure models for 3-D orchards considering spraying technologies in Southern Europe - Azimonti, Giovanna; Chueca, Patricia; Clementi, Emilio; Konstantinos P., Ferentinos; Garcerá Figueroa, Cruz; Grella, Marco; Luini, Mara; Marucco, Paolo; Mozzanini, Eric; Resecco, Marco; Tosti, Luca (Wiley, 2025)
Tree orchards like citrus, olives, apricot, peach and nuts, also known as 3D orchards, are typical crops of southern Europe (SEU) and present different vegetation characteristics (tree size, tree shape, foliar density, etc) and distinctive training systems and row and tree spacing in comparison with the ones used in apple and pear orchards in Central and Northern Europe, which are 3D orchards more typical of these zones. Furthermore, plant protection products (PPP) application techniques and their setting up are different as well. Moreover, the climatic conditions between North and South of Europe are pretty dissimilar. This could result in very different PPP exposure scenarios to those currently applied for risk assessment of pesticides where models developed for agro-climatic conditions typical of northern Europe are used. The multidisciplinarity and the specificity of the topic, in one hand related to registration but also to pesticide application equipment and training system of crops, have been addressed by a consortium with the appropriate expertise in the related fields. The present project characterised distribution of 3-D crops in Europe, addressing the ones present just in SEU and gathered information on equipment use, training system of crops and pesticide practices through dedicated surveys to farmers, sprayer inspection stations and manufacturers. A literature search was also performed to check whether studies specifically designed for 3-D orchards, in agroclimatic conditions of Southern Europe about drift and exposure models, are available in the public literature. From the few articles assessed as relevant to this project, some discrepancies between what is currently used and what is measured in those 3-D orchards of Southern use were identified, tackling the “worst-case” approach. The other key point raised by the literature search, which can greatly impact risk assessment procedures, is the importance of measuring not just sedimenting drift but also airborne spray drift: several studies report higher values for airborne drift compared to those found at ground level for the same downwind sampling distance .Overall, the results of this project provide valuable information to better address risk assessment of PPP in 3-D orchards, identifying major data gaps for exposure assessment that require further work and areas that require harmonisation